Upaya Guru PAI Dalam Meningkatkan Self-directed Learning di MTs Al Kautsar Ponorogo - Medina Nur Asyifah Purnama (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Teachers must be able to recognize and even be able to pay attention to the existence of students as unique individuals, both in terms of physical and intellectual development, as well as other characteristics that reflect their personality. The purpose of writing this paper is to find out the efforts of PAI teachers in increasing Self-directed Learning at MTs al Kautsar Ponorogo. Qualitative descriptive as the author's reference in the preparation of this work. The location is located at Ma Al-Kautsar, swinging Ponorogo. Observations, documentation and interviews as a reference for the author in the strategy to obtain data. The descriptive analysis chosen by the author to process the data obtained from the field and set forth in the research. The results of this work are 1). Using the awarding of grades or points as extrinsic motivation in improving students' Self-directed Learning by considering objectivity and affective values. 2). Give awards or rewards, which can motivate students and strengthen the relationship between teachers and students. 3). Imposing educational punishments to increase students' self-directed learning. 4). Build a good relationship with students. And 5). Giving praise that is appropriate and in accordance with student progress is an effective strategy in increasing student motivation and self-confidence.